Zbiory sztuki Kościoła Mariackiego w Gdańsku. Uwarunkowania historyczne - Noworyta-Kuklińska, Bożena (Archiwa, Biblioteki i Muzea Kościelne, 2016)
St. Mary's Church boasts an impressive Gothic interior of a high class, which houses a unique collection of works of art. It is the result of the patronage of extremely rich bourgeoisie of Gdańsk over four centuries - from 1400 to 1800- and also creative activities of the second half of the 20th century. It presents an extremely high artistic level, which owes to a sublime aesthetic taste of people from Gdańsk (often highly educated in European universities), who visited- because of their activities- important art centres in Europe, as well as their wealth thanks to which they could afford to hire the best artists.